Comics Problem-based Learning Model Implementation to Improve Students’ Learning Outcomes on Heat and Its Transmission - Intan Dwi Safitri; Beni Setiawan; Muhamad Arif Mahdiannur (Universitas Negeri Surabaya, 2022)
This study aimed to improve students’ learning outcomes on heat and its transmission using comics problem-based learning model as intervention program. This study used one group pretest-posttest design in the classroom natural setting. This study involved thirty-two students from 7th grade in one of Public Junior High School in the Sidoarjo Regency, East Java. Data were collected by using learning implementation observation forms, written test sheets, and students’ response questionnaire form. Based on the results of this intervention, we obtained a percentage of the lesson plans implementation 94.12% at the first meeting and 93.38% at the second meeting with very good category. The written test used pretest and posttest to measure the improvement in learning outcomes which got high normalized gain. The students’ responses toward the intervention categorized as strong and positive. The result of this study shows that the implication of the comics problem-based learning model is effective to improve the students’ learning outcomes, especially on heat and its transmission.